A questionnaire to assess rehabilitation patients' experiences with motivational interviewing consultation in the context of physical activity stimulation. Issue 15 (16th July 2020) - Hoekstra, Trynke; Alingh, Rolinde A.; de Vries, Hendrik S.; Bes, Rik; Hoekstra, Femke; van der Schans, Cees P.; Dekker, Rienk; Hettinga, Florentina J.; van der Woude, Lucas H. V.
Abstract: Purpose: The current article provides a description of the construction process of a short questionnaire that measures patients' experiences with a motivational interviewing consultation by a (sports) counselor in rehabilitation. Subsequently, results from confirmatory factor analyses are presented to investigate a first perspective on factorial construct validity of the questionnaire. Material and methods: Based on motivational interviewing literature, an initial item pool was created. All items were critically reviewed, resulting in the new "Evaluation of Motivational Interviewing Consultation on Active Lifestyle and Sports" questionnaire. The final items were determined by a confirmatory factor analysis based on 890 completed questionnaires. Results: The initial 26-item questionnaire consisted of four inter-correlated subscales. Factor analyses underpinned the proposed factors: acceptance, evocation, partnership, and non-adherent. After removing six items, an alternative model remained and showed an acceptable model fit. The internal consistency of the subscales derived varied from 0.70 to 0.90. Conclusion: The shortened questionnaire provides a feasible and easy to administer tool and may provide a cost saving method of assessing motivational interviewing fidelity from a patient's perspective in disability and rehabilitation. Implications for rehabilitation: Many persons with a physical disability do not obtain the recommended amount of physical activity in order to maintain health. Stimulation of a physically active lifestyle through motivational interviewing is promising. Measuring motivational interviewing treatment fidelity is time consuming and often from a counselor's perspective. We developed a short questionnaire facilitating the assessment of treatment fidelity at the side of the client. Our questionnaire provides a feasible and easy to administer tool for assessing MI fidelity in daily rehabilitation practice.